2019
DOI: 10.1016/j.cam.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Phase retrieval via Sparse Wirtinger Flow

Abstract: Phase retrieval(PR) problem is a kind of ill-condition inverse problem which can be found in various of applications. Utilizing the sparse priority, an algorithm called SWF(Sparse Wirtinger Flow) is proposed in this paper to deal with sparse PR problem based on the Wirtinger flow method. SWF firstly recovers the support of the signal and then updates the evaluation by hard thresholding method with an elaborate initialization. Theoretical analyses show that SWF has a geometric convergence for any k sparse n len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Reconstructing the target from Equation (7), where only the intensity of the echo signal is measured, is a typical PR problem [26,27,28,29,30,31,32,33,34,35]. Classic algorithms for solving PR problems include the GS algorithm, the PhaseLift algorithm, the WF algorithm, etc.…”
Section: Target Reconstruction Principle and Swfos Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…Reconstructing the target from Equation (7), where only the intensity of the echo signal is measured, is a typical PR problem [26,27,28,29,30,31,32,33,34,35]. Classic algorithms for solving PR problems include the GS algorithm, the PhaseLift algorithm, the WF algorithm, etc.…”
Section: Target Reconstruction Principle and Swfos Algorithmmentioning
confidence: 99%
“…In order to reduce the number of coding and sampling while increasing the speed of imaging, it is necessary to explore an algorithm that requires fewer samples. Recently, it was confirmed that utilizing the sparse prior information of the target can effectively reduce the samples required by the algorithm [33,34].…”
Section: Target Reconstruction Principle and Swfos Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…The antenna produces spatially diverse radiation patterns that vary as a function of the frequency sampled over the operational K-band (17.5-26.5 GHz). In [32], the authors use the more recent sparse WF algorithm proposed in [31] that allows to reduce the computational cost of the method.…”
Section: Introductionmentioning
confidence: 99%